Edukasi "Food Fear of Missing Out (FOMO)" dan Ancaman Diabetes Melitus Tipe 2 pada Remaja - Sofiyanti, Ida; Putri, Risma Aliviani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
The phenomenon of Fear of Missing Out (FOMO) toward viral food on social media encourages the excessive consumption of high-sugar and high-calorie foods among adolescents. This trend significantly increases the risk of Type 2 Diabetes Mellitus (T2DM) at a young age. This community service project aimed to raise awareness among students at SMA Muhammadiyah Sumowono regarding the dangers of "food FOMO" and its correlation with T2 DM. The method employed was interactive counseling utilizing PowerPoint presentations and concise flyers or posters. To measure the impact, pre-tests and post-tests were administered to 78 students from grades X and XI. The evaluation results showed a significant increase in student knowledge, with the average score rising from 65 in the pre-test to 88 in the post-test. This activity successfully provided a deep understanding of the health risks associated with impulsive eating patterns, emphasizing the urgency of school-based health education interventions to prevent a surge in Diabetes cases in the future. A recommendation for the school is to distribute digital copies of the flyers or a summary of the activity's findings to parents via WhatsApp groups.   ABSTRAK Fenomena Fear of Missing Out (FOMO) terhadap makanan viral di media sosial mendorong konsumsi berlebihan makanan tinggi gula dan kalori pada remaja, fenomena tersebut meningkatkan risiko Diabetes Melitus Tipe 2 (DM Tipe 2) di usia muda. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kesadaran siswa SMA Muhammadiyah Sumowono mengenai bahaya food FOMO dan korelasinya dengan DM Tipe 2. Metode yang digunakan adalah penyuluhan interaktif dengan media ppt dan flyer atau poster ringkas, dan dilakukan pre-test dan post-test untuk mengukur pemahaman kegiatan pada siswa kelas X dan XI yang berjumlah 78 mahasiswa. Hasil evaluasi menunjukkan peningkatan signifikan pengetahuan siswa, dari rata-rata 65 pada saat pretest menjadi 88 pada saat posttest. Kegiatan ini berhasil memberikan pemahaman mendalam mengenai risiko kesehatan akibat pola makan impulsif, menekankan urgensi intervensi edukasi kesehatan berbasis sekolah untuk mencegah lonjakan kasus DM di masa mendatang. Saran untuk sekolah yaitu menyebarkan salinan digital flyer atau ringkasan hasil kegiatan kepada grup WhatsApp orang tua siswa.